Case report: Large follicular thyroid carcinoma with multiple cervical lymph node metastases - Ye, Fei; Liao, Liyan; Tan, Wanlin; Gong, Yi; Li, Xiaodu; Niu, Chengcheng (Frontiers in Surgery, 2022)
Introduction: Follicular thyroid carcinoma (FTC) rarely metastasizes to regional lymph nodes, as they mainly metastasize through hematogenous route; in particular, a large FTC with only lateral lymph node metastasis and without distant metastasis has rarely been reported. Case report: We present a 66-year-old male patient with a progressively growing thyroid for more than 20 years, causing tracheal compression and narrowing. Neck ultrasonography, computed tomography (CT), magnetic resonance (MR) imaging and positron emission tomography–computed tomography (PET/CT) were carried out to obtain images of the thyroid and surrounding tissues. Total thyroidectomy and cervical lateral and central lymph node dissection were undertaken, and histopathological, and immunohistochemical evaluations and molecular pathology confirmed the diagnosis of FTC with multiple cervical lymph node metastases. Conclusion: We have reported a rare case of large FTC with diffuse nodal involvement but no distant metastases. We present the thyroid ultrasound, neck CT, MR and whole body PET/CT.